Effect of Ginseng Supplementation on Exercise Endurance as a Support for Cardiovascular Disease Management: A Systematic Review and Meta-Analysis - Angelika Szymańska; Anna Nowak; Anna Lipert; Ewa Kochan (Antioxidants)
Ginseng has multi-directional pharmacological properties. Some data suggest that ginseng can enhance physical endurance, which, in turn, leads to protection of the cardiovascular system. However, not all experiments are conclusive. For this reason, the main aim of this research was to perform a meta-analysis and review of studies published between the years 2013 and 2023 concerning the ginseng effect on physical performance in animal and human models. Medline, Pubmed, and ClinicalKey electronic databases were used to analyze data. The search strategy included the following criteria: ginseng and exercise; ginseng supplementation; and ginseng supplements. The results suggest that ginseng supplementation may have a positive effect on CK levels in animal studies. Similar observations were stated in relation to serum lactate and BUN. Furthermore, a human study showed a significant increase in exercise time to exhaustion and VO2 max after supplementation. The review of the literature and conducted meta-analysis identified that ginseng supplementation may have a positive effect on exercise endurance. Due to the fact that most of the current studies were based on animal models, further research on human models is needed to identify the most effective dosage or form of applied ginseng to be a supportive element in CVD management.